Comprehensive Midwifery Care For Mrs “F” With A Normal Pregnancy At The Caile Public Health Center - Irmawati; Rosnaeni; Mitha Alfiani; Andi Tenri Fajriani; Andi Nurlaily; Ely Kurniati (Jurnal Life Birth, 2022)
Comprehensive Midwifery Care is an upbringing that is given thoroughly starting from pregnancy, childbirth, newborns, nifas, neonates to family planning. The main goal of comprehensive midwifery care is to reduce morbidity and mortality (pain and death rates) in an effort to save mothers and babies focused on promotive and preventive efforts. The purpose of this case is to provide continuous midwifery care and document SOAP in pregnant women, maternity, newborns, unifas, neonates to birth control using varney management and in the form of in-person interviews, patient observation and home visits. Based on the results of comprehensive midwifery care in Mrs. "F" by conducting obstetric care independently and early handling, there was no involvement starting from pregnancy, childbirth, newborns, nifas, neonates and birth control. It is recommended to midwives to improve the quality of service to the health of the mother and baby. The conclusion is comprehensive midwifery care conducted on Mrs.F"starting from 36 weeks of gestation, maternity, BBL, neonates, nifas to family planning (KB), in accordance with midwifery service standards by using comprehensive midwifery care management and documented in the form of subjective data, objective data, data analysis and management (SOAP).